The Use of Selected Biomarkers, Phagocytic and Cholinesterase Activity to Detect the Effects of Dimethoate on Marine Mussel (Mytilus edulis) - YAQIN, KHUSNUL; LAY, BIBIANA WIDIATI; RIANI, ETTY (HAYATI Journal of Biosciences, 2009)
Effects of organophosphorous pesticide, dimethoate on blue mussels, Mytilus edulis using selected biomarkers have been studied. Mussels were exposed to serial dilutions of dimethoate, 7.88, 15.75, 31.35, and 63.00 µg/l including positive and negative controls for 14 days. The suppression effects of dimethoate on phagocytic activity significantly occurred at two lowest concentrations of dimethoate (7.88 and 15.75 µg/l), but stimulation effects significantly emerged at the following highest concentrations (31.35 and 63.00 µg/l). The declining tendency of the cholinesterase (ChE) activity (23% lower than the control) appeared when mussels exposed to 7.88 and 15.75 µg/l dimethoate. Moreover, the significant inhibition of the ChE activity occurred at 31.35 µg/l dimethoate exposure. This study suggested that the phagocytic and the ChE activity are useful biomarkers for assessing the affects of organophosporous pesticide, dimethoate on neuro-immune system of blue mussels, M. edulis. Key words: dimethoate, cholinesterase, phagocytic, blue mussels